Cobalamin Scarcity Modifies Carbon Allocation and Impairs DMSP Production Through Methionine Metabolism in the Haptophyte Microalgae Tisochrysis lutea - Nef, Charlotte; Henry, Céline; Nicolau, Élodie; Bérard, Jean-Baptiste; Hervé, Fabienne; Caruana, Amandine M. N.; Kaas, Raymond; Mairet, Francis; Garnier, Matthieu (Frontiers in Marine Science, 2020)
Cobalamin (vitamin B12) is a cobalt-containing enzymatic cofactor involved in methionine synthesis. Provided only by select bacteria and archaea in marine systems, this vitamin is known to limit primary production in different oceanic areas. Understanding the consequences of cobalamin limitation on phytoplankton physiology is of great interest, notably for cobalamin-dependent haptophytes that significantly contribute to oceanic carbon fixation and sulfur cycle through dimethyl sulfonio propionate (DMSP) synthesis. Here, the effect of cobalamin limitation was compared to nitrogen limitation on the model haptophyte Tisochrysis lutea grown in chemostats, combining comparative proteomics with the analysis of major macromolecules and specific osmolytes. Our results highlight the interconnection of carbon and DMSP metabolisms through the cobalamin-dependent methionine synthesis by showing that cobalamin scarcity impacts the mechanisms of carbon allocation and reduces DMSP quota. Conversely, proline production seemed to anticorrelate with cobalamin availability. In a boarder context, analysis of transcriptomes or genomes of main DMSP producers from different phytoplankton lineages suggests that most of them are cobalamin-dependent, which means that prokaryotic cobalamin synthesis exerts an important control on phytoplankton DMSP production in some regions of the world ocean.